1999
DOI: 10.1002/(sici)1521-3773(19990816)38:16<2439::aid-anie2439>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Donor/Acceptor Metallocenes: A New Structure Principle in Catalyst Design

Abstract: Suitable as highly effective polymerization catalysts is the new class of donor/acceptor metallocenes in which the rotation of the two pi ligands is restricted through the formation of a dative D(+)-->A(-) bond (see picture). Specifically optimized substitution patterns yield excellent properties for the synthesis of high-melting, highly crystalline thermoplastic materials, amorphous thermoplastic materials with high glass transition temperatures as well as polyolefin elastomers with low glass T(g).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…[ 7–10 ] Then, it was reported that metallocene catalysts immobilized on special supports were successfully used to produce UHMWPE. [ 11 ] The conventional metallocene catalysts such as CpTiCl 3 and CpZrCl 2 were reported to produce UHMWPE when immobilized on some special supports. [ 12,13 ] However, the processability of UHMWPE was poor because of the high melt viscosity which was caused by the extensive entanglement among molecular chains.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–10 ] Then, it was reported that metallocene catalysts immobilized on special supports were successfully used to produce UHMWPE. [ 11 ] The conventional metallocene catalysts such as CpTiCl 3 and CpZrCl 2 were reported to produce UHMWPE when immobilized on some special supports. [ 12,13 ] However, the processability of UHMWPE was poor because of the high melt viscosity which was caused by the extensive entanglement among molecular chains.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Metallocene catalysts were also used to produce UHMWPE, but the processes were much more complex than Ziegler-Natta catalyst. [28] When immobilized on particular supports (carbon nanotubes and graphene nanoplatelet), the metallocene catalysts such as CpTiCl 3 and CpZrCl 2 could produce UHMWPE. [29,30] The metallocene catalysts through single activity site, which were different from Ziegler-Natta catalyst, made the reaction rates stable and the products have narrow MWD.…”
Section: Introductionmentioning
confidence: 99%
“…Metallocene catalysts could also be used for UHMWPE, but they were not able to synthesize UHMWPE with as much ease as ZN catalysts did . The polymerization results of ≈100 different metallocene catalysts were surveyed by Alt and Köppl and indicated that the MW of the PEs produced was mostly well below the critical value of 10 6 g mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Resconi et al reported a hindered and covalently bridged meso‐ethylene‐bis(4,7‐dimethyl‐1‐indenyl) zirconium dichloride catalyst which was able to synthesize UHMWPE at 70 °C . Starzewski et al synthesized a series of bridged donor/acceptor metallocene catalysts with hindered structures to produce UHMWPE at temperature higher than 80 °C . Besides ZN and metallocene catalysts, several nonmetallocene catalysts were also reported to synthesize UHMWPE.…”
Section: Introductionmentioning
confidence: 99%